Wood/water relations of 15 south american lesser-used wood species - Welling, Johannes; Bartolo-Cuba, John Albert; Sánchez-Blanco, José Carlos; Ahrens-Castillo, Javier Luis; Ugarte-Oliva, José Alfredo (Maderas. Ciencia y Tecnología, 2023)
In the Amazonian forests of Perú a large variety of native wood species can be found, of which only a few are commercially exploited. Exploitation is focused on high density durable hardwoods for flooring applications. After selective logging of a few valuable trees the forests often are considered being “unproductive” because there is no market for most of the remaining trees. Having a long-term sustainable forest management and utilization plan in mind, a continuous extraction of more tree species is desirable. For opening out new markets for lesser-used species a concise knowledge of their physical and mechanical properties is essential. Fifteen lesser-used Peruvian wood species were investigated to characterize their wood/water relations. Density, shrinkage behavior, and sorption characteristics were determined. In addition, the functional relation between electrical resistance and moisture content was determined to provide a sound basis for non-destructive moisture content measurements.